Physical and Organoleptic Characteristics of Poultry Eggshell Powder Extracted with CH3COOH and NaOH - Diode Yonata; Siti Aminah; Wifaayatul Ainiyah; Afrilia Arifatul Lael; Anita Rahma Riyani (Universitas Muhammadiyah Semarang, 2017)
As food waste poultry eggshells contain harmful components, organic compounds, hard physical characteristics, rough, flavorful fishy and has a less attractive color when used as food. Extraction process with CH3COOH andNaOH is known to improve physical and organoleptic characteristics of egg powder eggshell. The generalpurpose of the research is to know the effect of CHCOOH and NaOH extraction on physical and organolepticcharacteristics of egg powder eggshell. The research method was experimental design using random completefactorial design, which consisted of 2 factors and 16 treatments is solvent type (Control, H2O, CH3COOH, andNaOH) and poultry eggshell (duck, quail, chicken race, and free-range chicken). Each treatment was repeated 3times, so that 48 units of experiments were obtained. The result data of physical characteristic test was analyzedusing Anova statistic method followed by further test of DMRT, while the test result of organoleptic characteristic was analyzed using Friedman statistic method followed by Wilcoxon test. The results showed that eggshell chicken eggs extracted with CH3COOH solution produces the best physical and organoleptic characteristics of eggshell flour. Keywords: Egg Shell, CH3COOH, NaOH, Physical, Organoleptic